Membrane type-1 matrix metalloproteinase stimulates tumour cell-induced platelet aggregation: role of receptor glycoproteins - Alonso-Escolano, David (2003)
1. Matrix metalloproteinase-2 (MMP-2) plays a role in agonist- and tumour cell-induced platelet aggregation (TCIPA). 2. MMP-2 is synthesized as a proenzyme and is activated at the cell surface by membrane type-1 matrix metalloproteinase (MT1-MMP, MMP-14). 3. The significance of tumour cell-associated MT1-MMP for TCIPA was investigated using human breast carcinoma MCF7 cells stably coexpressing the integrin αvβ3 with MT1-MMP, cells expressing αvβ3 alone and mock-transfected cells. 4. Western blot and zymography confirmed that αvβ3/MT1-MMP cells expressed MT1-MMP and efficiently processed proMMP-2 to MMP-2. 5. Aggregometry, phase-contrast and transmission electron microscopy and flow cytometry were used to characterize TCIPA induced by MCF7 cell lines. 6. The aggregating potency of cells was: αvβ3/MT1-MMP >αvβ3=mock cells, as shown by aggregometry and phase-contrast microscopy. 7. Electron microscopy revealed close, membrane–membrane interactions between activated platelets and αvβ3/MT1-MMP cells during TCIPA. 8. Inhibition of MMP-2 with the neutralizing anti-MMP-2 antibody (5 μg ml(−1)) and o-phenanthroline (100 μM) reduced aggregation induced by αvβ3/MT1-MMP cells. 9. TCIPA induced by αvβ3/MT1-MMP cells was also reduced by inhibiting the generation and actions of ADP with apyrase (250 μg ml(−1)) and 2-methylthio-AMP (2-MeSAMP) (30 μM), but not N(6)-methyl-2′-deoxyadenosine-3′,5′-bisphosphate (MRS2179) (30 μM). 10. Flow cytometry demonstrated that TCIPA enhanced expression of glycoprotein (GP) Ib and IIb/IIIa receptors not only on platelets but also on breast cancer cells. 11. Thus, (a) human breast carcinoma cell surface-associated MT1-MMP, via activating proMMP-2, stimulates TCIPA; (b) ADP amplifies the effects of MMPs via stimulation of P2Y(12) receptors and (c) both tumour- and platelet-derived GPIb and GPIIb/IIIa are involved in the aggregatory effects of MT1-MMP.